Analisis Pengelolaan Barang Milik Daerah di Pemerintah Kota Kotamobagu - Mokodompit, Deissy; Morasa, Jenny; Warongan, Jessy (Universitas Sam Ratulangi, 2017)
Abstract. The management of the asset of a local government should be implemented properly so that it can give a description of the prosperity of the local government. The objective of this study is to analyse the management of the asset of the local government of Kotamobagu. The research method used for this study is a qualitative case study which focuses on the government of Kotamobagu city as its object of research. The data were collected in three ways, namely in-depth interviews, observation and study documentation. The key Informants for this study were determined by using purposive sampling to get the accurate and relevant information. The criteria for informant selection are that the informants should be the head and the asset manager of the regional work units (SKPD). The in-depth interviews used semi-structured questions and took about 45 to 60 minutes. The triangulation method was used in testing the validity or the credibility of the data and the sources. The data transcript of the interviews was analyzed by giving a theme/coding to the transcript and by making conceptualized and scientific statements. The results are summarized in narrative text interpretation. The results shows that some obstacles in the management of the asset of the regions in the Government of the Kotamobagu City. There are 4 inhibiting factors, namely: (1) securing and maintenance asset, (2) valuation asset, (3) elimination asset, (4) compliance. Key Words: Local asset management, Regulation on local asset, Problem solving of local asset. Abstrak. Pengelolaan barang milik daerah merupakan sesuatu yang harus dilaksanakan dengan baik agar dapat memberikan gambaran tentang kekayaan daerah, serta dapat digunakan untuk dasar penyusunan laporan keuangan, Penelitian ini bertujuan menganalisis Pengelolaan Barang Milik Daerah pada Pemerintah Kota Kotamobagu. Metode penelitian menggunakan kualitatif dengan studi kasus dan Pemerintah Kota Kotamobagu sebagai objek penelitian. Data diperoleh melalui teknik wawancara mendalam, pengamatan, dan studi dokumentasi. Informan kunci ditentukan secara purposive untuk mendapatkan hasil informasi yang tepat dan akurat. Kriteria informan adalah Kepala SKPD, Pengurus dan Penyimpan Barang. Wawancara menggunakan In-depth interview jenis semi terstruktur selama 45 hingga 60 menit. Metode triangulasi digunakan dalam pengujian validitas atau kredibilitas data dansumber. Data transkrip yang diuraikan dari hasil wawancara dianalisis dengan metode analisis kemudian diberi tema/coding dan dilakukan konseptualisasi pernyataan ilmiah. Hasil interpretasi disimpulkan dalam teks naratif. Hasil penelitian menunjukkan ada beberapa kendala dalam pengelolaan barang milik daerah di Pemerintah Kota Kotamobagu. Ada 4 faktor penghambat: (1) pengamanan dan pemeliharaan, (2) penilaian, (3) penghapusan, (4) kepatuhan. Kata Kunci: Pengelolaan BMD, Regulasi BMD, Penyelesaian masalah BMD